EMG-based gesture recognition: CNN feature contribution and ablation study - Pinheiro, Miguel Marques Alves Maya (My University, 2024)
Electromyography (EMG)has emerged as a pivotal technology in biomedical engineering, offering valuable insights into muscle activity with significant applications in adaptive prosthetics. This thesis delves into the application of EMG signal classification to enhance gesture recognition for prosthetic control.Utilizing the GRABMyo dataset, which includes comprehensive EMG data from 43 participants performing various hand and wrist gestures, this study provides a robust platform for testing and validating classification algorithms. The data set was meticulously organized, ensuring clear separation between training and testing sets to facilitate rigorous evaluation.There search focuses on the implementation of Convolutional Neural Networks (CNNs) withan AleNet architecture for their superior feature extraction capabilities. An ablation study was conducted to systematically assess the influence of different neural network components on the model’s performance. By selectively disabling specific filters within the convolutional layers, the study aimed to identify the most critical features and components that significantly contribute to accurate gesturer ecognition.The objectives of this ablation study include optimizing the network by focusing on impactful elements and improving gesture classification accuracy. Following the ablation study, a recovery phase was implemented to restore and potentially enhance the model’s performance. This phase tested the network’sr esilience and adaptability, providing insights into its built-in redundancy and ability to compensate for lost functionalities through targeted training strategies. The recovery effort not only aimed to regain lost performance but also to deepen the understanding of which features and layers are most critical to the network’s operation. The fina phase involved validating the optimized model on a test set comprising participants not included in the training phase. To visually demonstrate the model’s effectiveness, the Unity engine was used to simulate the gestures based on the model’s classifications, offering a nintuitive and interactive representation of its capabilities.This visualization underscores the practical applications of the technology in adaptive prosthetics, bridging the gap between theoretical research and real-world implementation.

A eletromiografia (EMG) emergiu como uma tecnologia fundamental na engenharia biomédica, oferecendo insights valiosos sobre a atividade muscular com aplicações significativas em próteses adaptativas. Esta tese explora a aplicação da classificação de sinais EMG para melhorar o reconhecimento de gestos no controle de próteses. Utilizando o conjunto de dados GRABMyo, que inclui dados EMG abrangentes de 43 participantes realizando vários gestos com as mãos e os pulsos,este estudo fornece uma plataforma robusta para testar e validar algoritmos de classificação. O conjunto de dados foi meticulosamente organizado, garantindo uma separação clara entre os conjuntos de treino e teste para facilitar uma avaliação rigorosa. A pesquisa concentra-se na implementação de Convolutional Neural Networks (CNNs) com arquitetura AlexNet devido às suas capacidades superiores de extração de características. Um estudo de ablação foi conduzido para avaliar sistematicamente a influência de diferentes componentes da rede neural no desempenho do modelo. Ao desativar seletivamente filtros específicos dentro das camadas convolucionais, o estudo visou identificar as características e componentes mais críticos que contribuem significativamente para o reconhecimento preciso de gestos. Os objetivos deste estudo de ablação incluem a otimização da rede, focando em elementos impactantes e melhorando a precisão da classificação de gestos. Após o estudo de ablação,uma fase de recuperação foi implementada para restaurar e potencialmente melhorar o desempenho do modelo. Esta fase testou a resiliência e adaptabilidade da rede, obtendo maior clareza sobre sua redundância inerente e a capacidade de compensar funcionalidades perdidas através de estratégias de treino direcionadas. O esforço de recuperação não visou apenas recuperar o desempenho perdido, mas também aprofundar o entendimento de quais características e camadas são mais críticas para a operação da rede. A fase final envolveu a validação do modelo otimizado em um conjunto de teste composto por participantes não incluídos na fase de treinamento. Para demonstrar visualmente a eficácia do modelo, o motor Unity foi utilizado para simular os gestos com base nas classificações do modelo, oferecendo uma representação intuitiva e interativa de suas capacidades. Esta visualização sublinha as aplicações práticas da tecnologia em próteses adaptativas, fechando a lacuna entre a pesquisa teórica e a implementação no mundo real.
Keywords: Electromyography (EMG); Surface EMG (sEMG); EMG Signal Processing; Feature extraction; Gesture recognition; Prosthetic control; Machine learning; Deep learning; Convolutional neural networks; Ablation study; Model recovery